(untitled) - Bhatia, V. K. (London, 1993)
Genre analysis has a long-established tradition in literature, but interest in the analysis of non-literary genres has been very recent. This book examines the theory of genre analysis, looks at genre analysis in action, taking texts from a wide variety of genres and discusses the use of genre analysis in language teaching and language reform.
Keywords: Language and languages,Ngôn ngữ học; Style,Phong cách